2024
DOI: 10.1101/2024.02.08.579555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Related PP2C phosphatases Pic3 and Pic12 negatively regulate immunity in tomato toPseudomonas syringae

Fan Xia,
Ning Zhang,
Renee E. Smith
et al.

Abstract: Type 2C protein phosphatases (PP2Cs) constitute a large family in most plant species but relatively few of them have been implicated in immunity. To identify and characterize PP2C phosphatases that affect tomato immunity, we used CRISPR/Cas9 to generate loss-of-function mutants for 11 PP2C genes whose expression is altered in response to immune elicitors or pathogens. We report that two closely-related tomato PP2C phosphatases, Pic3 and Pic12, are involved in regulating resistance to the bacterial pathogen Pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 86 publications
1
2
0
Order By: Relevance
“…Phenotypic evaluation of plants inoculated with Pst DC3000Δ avrPtoB demonstrated that RG-pic14 mutants are more resistant to bacterial infection in their older but not younger leaves. In a related study, we observed a similar phenotype in plants carrying mutations in two PP2Cs sharing sequence similarity, Pic3 and Pic12 (Xia et al, 2024). In that work, RNA-seq analysis revealed that older leaves of RG-pic3 had significantly more differentially expressed genes related to defense compared to younger leaves.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Phenotypic evaluation of plants inoculated with Pst DC3000Δ avrPtoB demonstrated that RG-pic14 mutants are more resistant to bacterial infection in their older but not younger leaves. In a related study, we observed a similar phenotype in plants carrying mutations in two PP2Cs sharing sequence similarity, Pic3 and Pic12 (Xia et al, 2024). In that work, RNA-seq analysis revealed that older leaves of RG-pic3 had significantly more differentially expressed genes related to defense compared to younger leaves.…”
Section: Discussionsupporting
confidence: 58%
“…In a related study we found that two closely related PP2Cs, Pic3 and Pic12, play a partially redundant role in non-NTI plant immune responses (Xia et al, 2024). Pic14 is also related to another PP2C, Pic6 (Solyc05g052520), with both PP2Cs residing in clade E (Qiu et al, 2022) or clade B (Sobol et al, 2022) depending on the phylogenetic analysis and sharing 55% amino acid sequence identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation